A Comparative Study of the Bible and the Qur'an on the Creation of the Universe Using Julia Kristeva's Intertextuality Method - Askar, Ahmad; Aziz, Muhammad (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
This research aims to analyze and find the differences and similarities between the texts of the Qur'an and the Bible. One of them is the comparison of the Qur'an and the Bible about the creation of the universe. The method used is library research by using the intertextuality theory approach initiated by Julia Krsiteva to compare the Qur'an and the Bible. The results of this study show three principles of similarities and differences in the intertextuality of al-Qur'an and al-Kitab. First, the principle of haplology in Surah Al-Fussilat verse 11 explains the creation of the heavens and the earth, which is simpler than the explanation in the Bible. Second, the excerpt principle found in Surah Al-Anbiya:30 with the Bible 1:6 explains the beginning of the universe as a solid unity, then separated as it is today, namely the existence of the heavens and the earth. Third, the parallel principle regarding the similarity between texts in terms of themes and thoughts, such as in Surah Al-Baqarah:117 and the Bible 1:1-2. Both discuss and emphasize the theological side of understanding the verse of the creation of the universe. The fundamental difference lies in the details of the phases of the creation of the universe and the detailed order in which the creation of the universe took place.